CUBN as a novel locus for end-stage renal disease: insights from renal transplantation. - Anna Reznichenko (PLoS ONE, 2012)
Chronic kidney disease (CKD) is a complex disorder. As genome-wide association studies identified cubilin gene CUBN as a locus for albuminuria, and urinary protein loss is a risk factor for progressive CKD, we tested the hypothesis that common genetic variants in CUBN are associated with end-stage renal disease (ESRD) and proteinuria. First, a total of 1142 patients with ESRD, admitted for renal transplantation, and 1186 donors were genotyped for SNPs rs7918972 and rs1801239 (case-control study). The rs7918972 minor allele frequency (MAF) was higher in ESRD patients comparing to kidney donors, implicating an increased risk for ESRD (OR 1.39, p = 0.0004) in native kidneys. Second, after transplantation recipients were followed for 5.8 [3.8-9.2] years (longitudinal study) documenting ESRD in transplanted kidneys--graft failure (GF). During post-transplant follow-up 92 (9.6%) cases of death-censored GF occurred. Donor rs7918972 MAF, representing genotype of the transplanted kidney, was 16.3% in GF vs 10.7% in cases with functioning graft. Consistently, a multivariate Cox regression analysis showed that donor rs7918972 is a predictor of GF, although statistical significance was not reached (HR 1.53, p = 0.055). There was no association of recipient rs7918972 with GF. Rs1801239 was not associated with ESRD or GF. In line with an association with the outcome, donor rs7918972 was associated with elevated proteinuria levels cross-sectionally at 1 year after transplantation. Thus, we identified CUBN rs7918972 as a novel risk variant for renal function loss in two independent settings: ESRD in native kidneys and GF in transplanted kidneys.